2022
DOI: 10.1021/acsphyschemau.2c00022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Explosive Sensitivity with Effective Trigger Linkage Kinetics

Abstract: We present a simple linear model for ranking the drop weight impact sensitivity of organic explosives that is based explicitly on chemical kinetics. The model is parameterized to specific heats of explosion, Q, and Arrhenius kinetics for the onset of chemical reactions that are obtained from gas-phase Born-Oppenheimer molecular dynamics simulations for a chemically diverse set of 24 molecules. Reactive molecular dynamics simulations sample all possible decomposition pathways of the molecules with the appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 82 publications
1
41
0
Order By: Relevance
“…For instance, lead azide (Pb­(N 3 ) 2 ) has a high thermal stability, but is also highly sensitive to impact and friction insults and will even explosively decompose before it melts . This observation could potentially be explained by the abnormally high pre-exponential factor computed from Arrhenius plots of MD kinetic calculations, even though this explanation seems insufficient for our calculations. In the MD kinetic calculations, the maximum energy probed was 0.2 eV, while our lowest energy was 4 eV.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, lead azide (Pb­(N 3 ) 2 ) has a high thermal stability, but is also highly sensitive to impact and friction insults and will even explosively decompose before it melts . This observation could potentially be explained by the abnormally high pre-exponential factor computed from Arrhenius plots of MD kinetic calculations, even though this explanation seems insufficient for our calculations. In the MD kinetic calculations, the maximum energy probed was 0.2 eV, while our lowest energy was 4 eV.…”
Section: Discussionmentioning
confidence: 96%
“…66 While the chemistry and trigger linkage kinetics of the four PETN derivatives are clearly very similar, our drop weight impact testing reveals a precipitous increase in H 50 when nitrate esters are replaced by hydroxyl groups. In a recent publication, 32 we proposed that drop weight impact sensitivity depends jointly on the kinetics of trigger linkage rupture and the enthalpy of explosion via…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…We obtained a value of about γ ≈ 1.6 g/kcal, but we found that γ is somewhat system-dependent. Equation , which depends only on gas-phase thermochemistry, accounts for at best 70% of the variation in ln­( H 50 ), and we attribute the remaining 30% of the variation to condensed phase properties and chemistry that are not captured by the model . The intrinsic limitations associated with eq and the small numbers of families of explosive molecules that are suitable for parametrization of γ lead inevitably to significant uncertainties in the values of γ.…”
mentioning
confidence: 99%
See 2 more Smart Citations